Pengaruh Kecerdasan Intrapersonal Terhadap Hasil Belajar PPKn Peserta Didik kelas IV Sekolah Dasar Negeri - Pangestu, Deviyanti; Lestari, Wahyu; Surahman, Maman; Mustakim, Erni; Lestari, Yulita Dwi (Lentera: Jurnal Ilmiah Kependidikan, 2024)
The problem of this study is the low learning outcomes of Civics of fourth grade students of SD Negeri 5 Metro Pusat. This study aims to determine the positive and significant effect of intrapersonal intelligence on students' Civics learning outcomes. This research method is ex post facto with quantitative research type. Data collection techniques using questionnaires and documentation studies. The population in this study amounted to 59 students and the entire population was used as a research sample. The data collection instrument was a questionnaire with a Likert scale, which was previously tested for validity and reliability. Data analysis using simple linear regression. The results showed that there was a significant influence between intrapersonal intelligence on the learning outcomes of Civics of fourth grade students of SD Negeri 5 Metro Pusat in the 2023/2024 academic year.